Minimum effective betamethasone dosage on the neurological phenotype in patients with ataxia‐telangiectasia: a multicenter observer‐blind study. (26th March 2018) - Cirillo, E.; Del Giudice, E.; Micheli, R.; Cappellari, A. M.; Soresina, A.; Dellepiane, R. M.; Pietrogrande, M. C.; Dell'Era, L.; Specchia, F.; Pession, A.; Plebani, A.; Pignata, C.
Abstract : Background and purpose: Ataxia‐telangiectasia (A‐T) is a rare neurodegenerative disease, due to A‐T mutated (ATM) gene mutations, which typically presents with signs of progressive neurological dysfunction, cerebellar ataxia and uncoordinated movements. A‐T severely affects patients' quality of life. Successful treatment options are still not available. The aim of this multicenter study, performed with a blind evaluation procedure, was to define the minimal effective dosage of oral betamethasone, thus preventing the occurrence of side effects. Methods: Nine A‐T patients were enrolled to receive betamethasone at increasing dosages of 0.001, 0.005 and 0.01 mg/kg/day. Neurological assessment and the evaluation of quality of life were performed through the Scale for the Assessment and Rating of Ataxia and the Italian version of the Childhood Health Assessment Questionnaire (CHAQ) at each time‐point. The drug safety profile was evaluated. Patients were categorized as responders, partial responders and non‐responders. Results: Four of nine patients had a benefit at a dose of 0.005 mg/kg/day of oral betamethasone. Using the higher dosage, only one additional patient had a positive response. Conversely, a daily dose of 0.001 mg/kg was ineffective. A correlation between the serum adrenocorticotropic hormone levels and the clinical response was observed. Five of 30 CHAQ items improved in four patients. Conclusions: These data suggest that a short‐term betamethasone oral treatment, at a daily dosage of 0.005 mg/kg, is effective in some patients. Pre‐existing risk factors for side effects should be taken into account before therapy.